LEXICAL AND ANALYTIC FRAMEWORK FOR CROSS-CULTURAL PHILOSOPHY STUDENTS - Mamatkulova Bakhtijon Ravshanovna, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:  This  article  examines  the  integration  of  lexical  and  analytic frameworks  in  teaching  philosophy  to  cross-cultural  students.  The  lexical-analytic methodology  emphasizes  the  relationship  between  language,  cognition,  and philosophical reasoning in multilingual contexts. It focuses on how lexical structures and analytic reasoning can be applied to enhance comprehension of philosophical texts in  English.  The  study  argues  that  the  combined  use  of  linguistic  analysis  and philosophical interpretation allows international students to develop deeper conceptual understanding  and  more  effective  communication  skills.  This  interdisciplinary framework  strengthens  academic  writing,  critical  thinking,  and  the  appreciation  of linguistic diversity within philosophical discourse.